The relationships among work-family conflict, turnover intention and organizational citizenship behavior in the hospitality industry of Taiwan. Issue 8 (6th November 2017) - Wang, I-An; Lee, Bi-Wen; Wu, Shou-Tsung
Abstract : Purpose: The hospitality industry is well-known for its high turnover rate and shift work, both of which are direct precursors to work-family conflict (WFC) and family-work conflict (FWC). The purpose of this paper is to explore the impact of WFC and FWC on turnover intention (TI) and organizational citizenship behavior (OCB) via literature reviews and empirical analyses. Design/methodology/approach: The research data were collected using questionnaire surveys from employees working in the hospitality industries in Taiwan. The questionnaire consisted of two parts. The first part, which was conducted by interviewers, included questions about WFC/FWC and TI, and the second part, which was completed by pairing the respondents' answers with observations of supervisors, explored OCB. There were 325 effective samples collected. Reliability and validity were confirmed using confirmatory factor analysis. Sample properties were analyzed using descriptive statistical analysis, and the relationship among control variables, predictor variables and outcome variables were explored via correlation analysis, independent t -test and one-way ANOVA. Finally, the study hypotheses were verified by structural equation modeling. Findings: The paper attempted to identify the relationships among WFC/FWC, TI and OCB. The results revealed that: WFC and FWC were positively related to TI; WFC and FWC were negatively related to OCB; and TI was negatively related to OCB. Practical implications: While the policy of tourism development has been promoted proactively by Taiwan's Government in recent years, there are insufficient studies describing the relationships among WFC, TI and OCB with respect to hospitality employees. The findings from this study may contribute to human resource management and strategy development. Originality/value: Because OCB is minimally regarded as an outcome variable, the results of this study support the relationships among OCB, WFC/FWC and TI. The results of this study will be of great benefit to supervisors as they seek to manage effectively human resources and improve and control the relationships among OCB, WFC/FWC and TI. The findings will also be of benefit to future studies.